The Regional Western Sweden SOM Survey 2002 - SOM Institute, University of Gothenburg (University of Gothenburg, 2006)
Western SOM has been conducted yearly since 1992, but was initially limited to residents of Gothenburg and its surrounding municipalities. In 1998, the survey was extended to include the entire Västra Götaland County plus the municipality of Kungsbacka.

The purpose of the regional surveys is to enable SOM researchers to study attitudes and behaviour linked to local and regional issues. They emphasise public services and media, although many of the questions are identical with those used in National SOM in order to make the answers comparable both between the regions and with Sweden at large.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena

Detta är den elfte studien i serien SOM-undersökningar genomförda i Västsverige. Undersökningen genomfördes med två olika enkätformulär: ett riktat till invånarna i Göteborg med kranskommuner och ett till dem hemmahörande i resterande delar av Västra Götaland. Enkätformulären innehåller till största delen gemensamma frågor. Några frågor är dock enbart ställda i en av de två enkäterna; framför allt handlar det om frågor enbart ställda i formuläret till invånarna i Göteborgsregionen. Båda enkäterna innehåller frågeområdena: Massmedier; Politik och samhälle; Samhälle och service; Kultur- och naturmiljö; Trygghet och säkerhet; Teknikinnehav och internet; Aktiviteter och fritidsvanor; Arbetsliv; och Om dig själv. Göteborgsregionens enkät innehöll även frågeområdena: Göteborg-Posten; samt Göteborgs kommun.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 2002
Väst-SOM 2002
Keywords: public sector; offentlig sektor; political interest; politiskt intresse; newspaper readership; tidnings läsekrets; membership; medlemskap; party identification; partiidentifikation; public services; offentlig service; book use; bokanvändning; news; nyheter; labour and employment; arbete och sysselsättning; political participation; politiskt deltagande; government; regering; television viewing; tv-tittande; language skills; språkfärdigheter; internet; internet; democracy; demokrati; internal politics; inrikespolitik; visits to recreational facilities; fritidsanläggningsbesök; political parties; politiska partier; football team supporters; fotbollssupporter; schools; skolor; politicians; politiker; community behaviour; samhällsdeltagande; recreational facilities; fritidsanläggningar; clubs; föreningar; cultural participation; kulturdeltagande; cultural facilities; kulturanläggningar; cultural heritage; kulturarv; leisure time activities; fritidsaktiviteter; personal safety; personlig trygghet; radio listening; radiolyssnande; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Cultural activities and participation; Kulturaktiviteter och deltagande; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap